Personal, Social, and Environmental Correlates of Walking to School Behaviors: Case Study in Austin, Texas. (2008) - Zhu, Xuemei; Arch, B.; Lee, Chanam
Abstract : Walking is an affordable and environmentally clean mode of transportation that can bring additional benefits as healthy physical activity. This cross-sectional study examines the prevalence and correlates of walking to or from school in eight elementary schools in Austin, Texas, which have high percentages of low-income, Hispanic students. A survey of 1, 281 parents was conducted, including questions about personal, social, and environmental factors that may influence their decisions on the children's school transportation. Binary logistic regressions were used to estimate the odds of choosing walking as the children's typical school travel mode. The results showed that walking was a typical mode for 28 and 34% of trips to and from school, respectively, and mostly accompanied by an adult. Parents' education level, family's car ownership, children's and parents' personal barriers, and having the school bus service reduced the likelihood of walking, while positive peer influences encouraged walking. Among the physical environmental factors, living close to school was the strongest positive predictor; safety concerns and the presence of highway or freeway en route were negative correlates. We concluded that the location of school is a key, as it determines the travel distance and the presence of highway or freeway en route. In addition to environmental improvements, educational and other assistance programs are needed for both parents and children to overcome their personal barriers and safety concerns. Health and disparity issues require further attention, as many underprivileged children have no other means of school transportation but walking in unsafe and poor environments.